Development of hybrid cooling method with PCM and Al2O3 nanofluid in aluminium minichannels using heat source model of Li-ion batteries. (September 2020) - Mashayekhi, Masoud; Houshfar, Ehsan; Ashjaee, Mehdi
Highlights: Various thermal management systems are experimentally studied at three heat fluxes. Active/passive methods failed to keep battery within the safety limit at high rates. Copper metal foam increased heat dissipation to surrounding in battery pack. Al2 O3 -water nanofluid increased heat transfer from battery pack to surrounding. Increment in convective heat transfer was efficient in high discharge rates. Abstract: Lithium ion batteries are considered as the main energy storage option. High temperatures cause capacity fading and can even produce fire. It is, therefore, essential to design an effective thermal management system (TMS) to keep battery temperature in the safe range. In this study, thermal response of lithium ion batteries is investigated in high discharge rates with a new TMS combining active and passive methods. Refined paraffin in blockform (P 42–44 #107150) combined with porous copper metal foam was considered as the passive part and aluminium mini-channel containing coolant flow was regarded as the active part of TMS. The experiments were conducted at three different Reynold numbers in active and hybrid methods and it was shown that at higher flowrates the maximum temperature is lower. The research has also shown that passive cooling was inefficient in keeping the battery temperature below the safety limit of 60 °C in high discharge rates. The hybrid thermal management system (HTMS) reduced the steady-state temperature of batteries by 19.5% compared to active method at a Reynolds number of 340 and heat generation power of 3.7 W. The active method was also ineffective in controlling the battery temperature at high heat generation power levels while HTMS showed an appropriate thermal performance at the same condition. Furthermore, effect of utilizing Al2 O3 -water nanofluid with two different volume fractions was investigated in both active and hybrid systems. It was shown that, compared to the base case with water flow, nanofluid can reduce the maximum temperature of batteries by 15.5% and 8.5% in active and hybrid methods, respectively.